2012
DOI: 10.1128/mcb.06166-11
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Driven by a Master Regulator of Hematopoiesis

Abstract: Developmental and homeostatic remodeling of cellular organelles is mediated by a complex process termed autophagy. The cohort of proteins that constitute the autophagy machinery functions in a multistep biochemical pathway. Though components of the autophagy machinery are broadly expressed, autophagy can occur in specialized cellular contexts, and mechanisms underlying cell-type-specific autophagy are poorly understood. We demonstrate that the master regulator of hematopoiesis, GATA-1, directly activates trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
122
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 59 publications
6
122
0
1
Order By: Relevance
“…This result is consistent with previous reports demonstrating that FOXO3A-and GATA-1-driven pro-autophagy gene programs function as a cytoprotective mechanism in HSCs and erythroid progenitors. 32,36 However, RCAD KO mice appear to exhibit more severe phenotype comparing to either ATG7 or FIP200 KO mice. RCAD KO embryos usually died around E11.5.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with previous reports demonstrating that FOXO3A-and GATA-1-driven pro-autophagy gene programs function as a cytoprotective mechanism in HSCs and erythroid progenitors. 32,36 However, RCAD KO mice appear to exhibit more severe phenotype comparing to either ATG7 or FIP200 KO mice. RCAD KO embryos usually died around E11.5.…”
Section: Discussionmentioning
confidence: 99%
“…We also report that the deletion of GLN3 increases the expression of ATG8 and ATG29 in growing conditions, suggesting that the Gln3 protein is directly or indirectly involved in the repression of some ATG genes. Previous studies showed that the mammalian GATA1 and GATA4 transcription factors are involved in the expression of several autophagy-related genes, 20,23 suggesting that the function of the GATA family members in regulating autophagy is conserved from yeast to mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that the transcriptional regulation of ATG genes is critical for autophagy: the level of Atg8, for example, correlates with autophagosome size, 16 that of Atg9 correlates with their number, 17 and the amount of Atg7 modulates autophagy amplitude. 18 In higher eukaryotes the family of FOXO transcription factors, GATA1 as well as the master regulator TFEB, activate autophagy, [19][20][21] while ZKSCAN3 and GATA4 are involved in the repression of mammalian autophagy-related genes. [22][23] In yeast, recent studies characterized Ume6 and Pho23 as transcriptional repressors of ATG genes and negative regulators of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Along these lines, the erythroid transcription factor GATA1 and its coregulator Friend of GATA1 induce the transcription of multiple genes encoding autophagy components; this developmentally regulated transcriptional response is coupled to increases in autophagosome number as well as the percent of cells that contain autophagosomes. 466 Finally, CEBPB/C/EBPβ is a transcription factor that regulates autophagy in response to the circadian cycle. 467 Although less work has been done on post-transcriptional regulation, several studies implicate microRNAs in controlling the expression of proteins associated with autophagy.…”
mentioning
confidence: 99%